PBL과 코칭을 활용한 대학 교양수업 개발 연구 －인성 교과목을 중심으로 - 조성진 (교양교육연구, 14(4), 2020)
본 연구의 목적은 대학에서 교양수업으로 진행된 인성 교과목에 PBL과 코칭을 활용했을 때 일어난다양한 현상들을 분석하는 것이다. 이를 위해 대학생 310명을 연구대상자로 선정했고, 그들이 작성한성찰일지, 평가지, 인터뷰 자료와 교수자가 작성한 관찰일지 등을 근거이론에 따라 분석했다. 이를 통해 얻은 결과를 요약하면 다음과 같다. 첫째, 대학생들은 새로운 수업방식에 매력을 느꼈고, 의사소통 능력과 문제 해결 능력이 향상되었으며, 비판적인 사고 확장을 경험한 것으로 확인되었다. 둘째, 대학생들은 처음에는 PBL 방식을 낯설고 부담스럽게 생각했지만, 수업이 진행되면서 재미와흥미를 느꼈으며, 수업에 만족하는 것으로 확인되었다. 셋째, 대학생들은 자신의 가치관을 정립하는계기를 가졌고, 인성함양의 중요성을 인식했다. 넷째, 대학생들은 교수자의 수업 운영전략과 유연한태도에 따라 수업에 대한 흥미를 갖고 참여하는 것으로 나타났다. 마지막으로, 다양한 디지털 자원을적극적으로 활용하는 것이 수업 효과를 더욱 높이는 것으로 나타났다. 이런 결과는 대학교육 혁신 차원에서 교양수업에 PBL 방식을 적극적으로 도입하고, 학습 촉진자역할을 하는 교수자의 역량 강화를 위해 코칭을 도입할 필요가 있음을 시사하고 있다. The purpose of this study was to analyze various phenomena that occurred when Problem Based Learning(PBL) and coaching were used for personality courses conducted in liberal arts classes at universities. To achieve this end, 310 college students were selected as study subjects, and their reflection journals, evaluation papers, interview materials, and the instructor's observation journals were analyzed according to the grounded theory. The results obtained through this study are as follows. First, it was confirmed that college students were attracted to the new teaching method, the improved communication skills and problem-solving skills, and that they also experienced an expansion in their critical thinking abilities. Second, college students initially thought of the PBL method as unfamiliar and burdensome, but as the class progressed, they found it to be enjoyable and interesting and eventually they were satisfied with the class. Third, college students had an opportunity to establish their own values and recognized the importance of building personality. Fourth, college students were found to participate with interest in the class according to the teaching strategy and flexible attitude of the professor. Finally, it has been shown that if digital resources are actively used, the effectiveness of the lessons is enhanced. These results suggest that it is necessary to actively introduce the PBL method to the liberal arts classes in order to innovate college education. Moreover, we should also introduce coaching to strengthen the capacity of tutors who serve as learning facilitators. KCI Citation Count: 2